2002
DOI: 10.1161/hs0202.102600
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Hyperthermia Is Associated With Cognitive Dysfunction After Coronary Artery Bypass Graft Surgery

Abstract: Background and Purpose-Temperature is a well-known modulator of experimental cerebral injury. We hypothesized that hyperthermia would be associated with a worsened cognitive outcome after coronary artery bypass graft surgery (CABG). Methods-Three hundred consenting patients undergoing cardiopulmonary bypass for CABG had hourly postoperative temperatures recorded. The degree of postoperative hyperthermia was determined by using the maximum temperature within the first 24 hours as well as by calculating the area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(94 citation statements)
references
References 42 publications
0
93
0
1
Order By: Relevance
“…However, specific maneuvers performed during the surgical procedure, eg, manipulation of an atherosclerotic ascending aorta, prolonged cardiopulmonary bypass time, and cerebral hyperthermia have been associated with poorer neurologic outcome. 7,14,15 Most studies examining predictors of POCDs have identified both patient-related and surgery-related factors, suggesting a multi-factorial etiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, specific maneuvers performed during the surgical procedure, eg, manipulation of an atherosclerotic ascending aorta, prolonged cardiopulmonary bypass time, and cerebral hyperthermia have been associated with poorer neurologic outcome. 7,14,15 Most studies examining predictors of POCDs have identified both patient-related and surgery-related factors, suggesting a multi-factorial etiology.…”
Section: Discussionmentioning
confidence: 99%
“…19 Yet other studies have shown a detrimental effect of hyperthermia on cognitive outcomes. 15 The heterogeneity in the method, degree, and duration of hypothermia used are probably responsible, in large part, for the variability in the findings. A key feature of our study is the use of sustained hypothermia (without rewarming) compared with other trials, which may protect against the potentially harmful effects of cerebral hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The mechanism(s) of POCD remains elusive, although several contributing factors have been proposed, 1 including the exacerbation of preoperative cognitive impairment, 5 genetic predisposition, cerebral embolism/hypoperfusion, hemodilution, hyperglycemia, anesthetic neurotoxicity, [6][7][8] and perioperative hyperthermia. 9 In addition to these mechanisms, cerebral inflammation in response to embolic and other events during CPB, manifested by transcerebral platelet activation, 10 has also been proposed as a mechanism linking POCD to cardiac surgery. 10,11 Given the mechanistic uncertainty behind POCD, it is not surprising that few interventions to date have been successful in ameliorating POCD in patients undergoing cardiac surgery.…”
Section: Résumémentioning
confidence: 99%
“…1 Similarly, postoperative hyperthermia has also been reported to have adverse neurocognitive consequences. 4 These clinical deleterious effects of hyperthermia have been mirrored experimentally where the risk of damage after cerebral ischemia is increased by hyperthermia. 6 These factors suggest that either hyperthermia causes some de novo injury or further complicates injury once it has already occurred.…”
Section: Objectifmentioning
confidence: 99%